Synthesis, Structure and Photoluminescent Properties of a New Ba(II)-Doped Cd(II) Coordination Polymer. Issue 5 (3rd May 2016) - Zhou, Pingping; Li, Xiaohui; Dong, Yanli; Liu, Huimin
Abstract : A new heterometallic compound, namely [CdBa(tdc)2 (DMF)2 (H2 O)]n (1 H2 tdc = 2, 5-thiophenedicarboxylic acid, DMF = N, N′-dimethylformamide), has been solvothermally synthesized and characterized by elemental analysis and single crystal X-ray diffraction. Compound 1 features a complicated three-dimensional (3D) framework based on heterometallic -Cd-COO-Ban - inorganic chains. In addition, the luminescent properties of this compound were also investigated at room temperature.